High-Efficiency Dielectric Reflectarray Antennas With Ultra-Wideband Characteristics - Eun-Cheol Choi (IEEE, 2021)
In this study, a K-band offset dielectric reflectarray antenna, having high aperture efficiency and ultra-wideband characteristics, was designed. A column-type dielectric unit cell was employed for the dielectric reflectarray elements. To obtain the ultra-wideband characteristics, an effective arrangement of the dielectric elements was implemented by considering the relative phase requirement. In addition, the real phase error and element patterns were calculated and analyzed using the equivalence principle and full-wave simulations. The prototype of the dielectric reflectarray antenna was fabricated by milling a dielectric sheet. The performance of the proposed antenna was measured and observed to be in good agreement with the simulation results. The measured results demonstrate that the maximum aperture efficiency was 63% at 22 GHz and bandwidth for an aperture efficiency exceeding 40% was 42.5%. The achieved results signified the importance of the arrangement strategy of the elements to achieve better efficiency and wider bandwidth performances.